2013
DOI: 10.1111/cen.12064
|View full text |Cite
|
Sign up to set email alerts
|

Relation between lipoprotein subfractions and TSH levels in the cardiovascular risk among women with subclinical hypothyroidism

Abstract: Our findings indicate that cardiovascular risk is affected in patients with TSH levels over 10 mIU/l, who have a lipid profile characteristic of atherogenic dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
15
0
4
Order By: Relevance
“…Regarding lipoproteins subclasses, Hernadez-Mijares found, similarly to the current study, increasing proportion of LDL pattern B profile patients from euthyroid to SCH(26). However, they did not address LDL subclasses across the euthyroidism range.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding lipoproteins subclasses, Hernadez-Mijares found, similarly to the current study, increasing proportion of LDL pattern B profile patients from euthyroid to SCH(26). However, they did not address LDL subclasses across the euthyroidism range.…”
Section: Discussionsupporting
confidence: 88%
“…However, a large cross-sectional study conducted in Australia, did not show any difference in the prevalence of hypertension or mean SBP/DBP values between euthyroid subjects or those with SH (23), as did a more recent study in Spain (24). Interestingly, even mild differences in serum TSH (within the reference range) have been associated with signif- icant differences in DBP (25), although others did not find any difference (26). The reduction in SBP and DBP observed in our study and its clinical implications need to be further confirmed in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…The studies have shown SCH to be associated with highly atherogenic pattern B of LDL-C subfractions. 26 It has been reported that as a marker of lipoprotein particle size, the value of LDL and VLDL adds predictive value beyond that of the individual lipids, and/or TC/HDL-C ratio. 27 This could also indicate that SCH is associated with high LDL & VLDL and thereby a highly atherogenic lipid profile.…”
Section: Discussionmentioning
confidence: 99%